PENERAPAN AKUNTANSI LINGKUNGAN DALAM PENGELOLAAN LIMBAH: STUDI PADA PENCUCIAN MOBIL - Nida Fiya Umaini; Sihabudin, Sihabudin; Arimurti, Trias (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2024)
The car wash business is one of the types of businesses that generates waste that can pollute the environment and endanger the surrounding community. The research method used is descriptive research with a qualitative approach. Data collection was obtained using source triangulation and method triangulation through interviews and observations. The participants in this study are car wash businesses in Karawang Regency. Informants in this study consist of key informants, main informants, and supporting informants. Data analysis techniques used are data reduction, data presentation, and conclusion drawing. The results of this study indicate that car wash businesses in Karawang Regency do not yet know and understand environmental accounting, and have not implemented environmental costs in their financial reports. However, there are environmental costs incurred, one of which is the cost of internal environmental failures.